Latinos and the 2016 election : Latino resistance and the election of Donald Trump - Sanchez, Gabriel R., 1979-; Fraga, Luis Ricardo; Ramírez, Ricardo, 1973- (Latinos in the United States series., 2020)
"The essays in this volume provide a detailed analysis of the state and national impact Latino voters had in the 2016 election"--